Prospek Lidi Kelapa Sawit Bagi Petani Sawit Rakyat Dan Perkebunan Di Kecamatan Pantai Labu Kabupaten Deli Serdang - Yuni Syahputri; Hesti Sabrina; Raudha Anggraini Tarigan; Muhammad Usman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Oil palm is a plant that has benefits for humans by processing its fruit into oil, besides that the fruit and trunk of oil palm can also be used as particle board. The fronds of oil palms have so far only become waste and are not utilized properly. Palm oil sticks are also no less important in providing additional income to the palm oil farmer. But because of the lack or lack of knowledge of the community in managing palm sticks into a craft that has economic and aesthetic selling value, so many branches or palm fronds are not produced properly. So that it causes piles of palm fronds on plantation land. The method used is the Knowledge sharing method. Knowledge sharing method. Knowledge sharing is a method or activity in knowledge management that is used to provide and disseminate knowledge, ideas, experiences, or skills from a person, department, organization, agency, or company to create a basic need for cooperation.